Attracting Foreign Direct Investment as an Economic Challenge for Ukraine in the Context of Globalization - Bezuhla, Liudmyla; Безугла, Людмила; Kinash, Iryna; Кінаш, Ірина; Andrusiv, Uliana; Андрусів, Ульяна; Dovgal, Olena; Довгаль, Олена (Ivano-Frankovskiy natsional'nyy tekhnicheskiy universitet nefti i gaza, 2019)
The paper reflects topical issues related to the attraction of foreign direct investment. The various dynamics of direct foreign investments into and from the economy of Ukraine are investigated. Tendencies of changing indicators are established. The emphasis is placed on the fact that the volume of direct foreign investments per person remains low. Foreign direct investment is mostly from the EU. It is concluded that in recent years a lot of foreign investors have lost interest in the Ukrainian economy. The main reasons for this comprise the risks that we associate with economic and political instability; the corruption of power structures, the influence of negative factors, both social and geopolitical. Problems in the field of attraction of foreign investments, which require urgent solution, are revealed. Modeling of foreign direct investments into the Ukrainian economy has been conducted by the method of trend extrapolation and predicted values of the indicator. The directions, aimed at strengthening of investment attractiveness of Ukraine, are grounded. У статті відображені актуальні питання, пов'язані із залученням прямих іноземних інвестицій. Досліджено різна динаміка прямих іноземних інвестицій в економіку України та з неї. Встановлено тенденції зміни показників. Акцент зроблений на тому, що обсяг прямих іноземних інвестицій на людину залишається низьким. Прямі іноземні інвестиції в основному надходять з ЄС. Зроблено висновок, що в останні роки багато іноземних інвесторів втратили інтерес до української економіки. Основними причинами цього є ризики, які ми пов'язуємо з економічною і політичною нестабільністю; корумпованість владних структур, вплив негативних чинників, як соціальних, так і геополітичних. Виявлено проблеми в сфері залучення іноземних інвестицій, що вимагають невідкладного рішення. Моделювання прямих іноземних інвестицій в економіку України проводилося методом екстраполяції тренда і прогнозних значень показника. Обґрунтовано напрями, спрямовані на посилення інвестиційної привабливості України.
Залучення прямих іноземних інвестицій як економічний виклик для України в умовах глобалізації
Keywords: foreign investment; іноземні інвестиції; capital investment; капіталовкладення; rating; рейтинг; investment attractiveness; інвестиційна привабливість; modeling; моделювання